2014
DOI: 10.1021/jo5001059
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized 4-Carboxy- and 4-Keto-2,3-dihydropyrroles via Ni(II)-Catalyzed Nucleophilic Amine Ring-Opening Cyclizations of Cyclopropanes

Abstract: A general synthetic approach to vinylogous 4-carboxy- and 4-keto-2,3-dihydropyrroles is reported using Ni(ClO4)2·6H2O as a Lewis acid catalyst for nucleophilic amine ring-opening cyclizations of donor-acceptor (D-A) cyclopropanes. This methodology provided good to excellent yields of functionalized 2,3-dihydropyrroles under milder reaction conditions than previously reported and is amenable to a variety of D-A cyclopropanes and primary amines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(35 citation statements)
references
References 52 publications
0
35
0
Order By: Relevance
“…Recently, our group has demonstrated that a chiral N , N′ ‐dioxide/Sc III complex was able to catalyze the ring‐opening reaction of cyclopropyl ketones with amines efficiently, thus generating chiral 2,3‐dihydropyrroles in excellent results. The process is thought to proceed through nucleophilic ring opening of the cyclopropyl ketone to generate A , then intramolecular nucleophilic addition to afford the intermediate B , with subsequent dehydration to give the 2,3‐dihydropyrrole product (path a, Scheme ) ,,…”
Section: Methodsmentioning
confidence: 99%
“…Recently, our group has demonstrated that a chiral N , N′ ‐dioxide/Sc III complex was able to catalyze the ring‐opening reaction of cyclopropyl ketones with amines efficiently, thus generating chiral 2,3‐dihydropyrroles in excellent results. The process is thought to proceed through nucleophilic ring opening of the cyclopropyl ketone to generate A , then intramolecular nucleophilic addition to afford the intermediate B , with subsequent dehydration to give the 2,3‐dihydropyrrole product (path a, Scheme ) ,,…”
Section: Methodsmentioning
confidence: 99%
“…Synthesis of 20 a. Compound 19 a was synthesized according to a literature method 29. Compound 19 a (0.2 mmol, 61.4 mg) was mixed with FeCl 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Synthesis of 2-pyrrolines by nickel catalysis. France et al 131 developed a general synthetic approach to 4-carboxyand 4-keto-2,3-dihydropyrroles 242 using Ni(ClO 4 ) 2 $6H 2 O as a Lewis acid catalyst via nucleophilic primary amine ringopening cyclizations of donor-acceptor (D-A) cyclopropanes 241 (Scheme 77). The optimized conditions were 15 mol% of Ni(ClO 4 ) 2 $6H 2 O with 1.2 equiv.…”
Section: Synthesis Of 2-pyrrolinesmentioning
confidence: 99%